Developing English Reading Material for The Tenth Grade of Computer and Network Engineering Students at SMK N 4 Payakumbuh - Wahyuningsih Wahyuningsih; Veni Roza; Eliza Eliza; Genta Sakti (Lembaga Pengembangan Kinerja Dosen, 2023)
There are several problems found in this research, such the material used by teacher was not related to the major, textbook for students was not provide the material related to their major, and the material only taken from the internet by teacher randomly. This research is research and development which uses the theory of Sugiyono. The stages in this development are research, developing, validation, and testing. The subjects in this study were 36 students from the tenth grade of Computer and Network Engineering. The need analysis shows, students want to learn reading material that is related to their major and useful when they work after graduation. For validation by expert, the English reading material is categorized as